8.0k views
0 votes
- 8x + y=-6
16x + 2y = 3
Solve by substitution

1 Answer

7 votes

Hey there!

To start, substitution is isolating one variable in one equation in a system and plugging it into the second equation for the variable isolated.

In this case, because y in the first equation has a coefficient of 1, it is easiest to use. So now, isolate y:

-8x + y = -6

y = 8x - 6

Now that you have solved for y, plug 8x - 6 into the y value of the second equation and solve for x:

16x + 2(8x-6) = 3

16x + 16x - 12 = 3

32x - 12 = 3

32x = 15

x = 15/32

Now that you have your x value, plug it into your first equation for x and solve for y:

-8(15/32) + y = -6

-15/4 + y = -6

y= -6 + 15/4

y= -9/4

Therefore, your final answer would be x = 15/32 and y = -9/2 or the point pair (15/32, -9/2).

User Reiner Gerecke
by
5.4k points